DARI MONOPOLI HINGGA PELABUHAN BEBAS: AKTIVITAS PERDAGANGAN DI KARESIDENAN TERNATE 1854-1930 - Rustam Hasim (SASDAYA: Gadjah Mada Journal of Humanities, 2019)
This paper discusses trading practices conducted in the Ternate Residency after the Dutch turned the port in the residence as a free port in 1854. In line with this policy, several major export and import materials supported the growth of the port meanwhile clove commodities did not become superior goods due to Hongotochten and extirpate policies in the VOC period. This fact shows that the policy of turning into the free port in 1854 was not only apart of the intention to control the economic resources within Ternate Area, but also to create Ternate as a colonial area under the Dutch’s control. This, in fact, opened a new chapter for trading activities in the region. The purpose of this policy is to attract and concentrate the commercial activities of the indigenous population to the free port under the supervision of the Dutch colonial for they hoped to prevent an indigenous merchant from establishing trade relations with other European nations. This study found that in 1854 the Dutch government made Ternate a free port is the implementation of a free port as the first step to protect economic interests, besides it is intended to place the Dutch in maintaining trade control in the territory of the colony.